(untitled) - Trione, Sinibaldo Oscar (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Influencia de la profundidad de estratificación de estacas de vid sobre su capacidad de enraizamiento (1963)

(untitled)
The influence of the depth of stratification of Vitis vinífera L. cv. Malbec cuttings were studied in relation to their rooting capacity. The trial was carried out under field condition at 5, 10, 20, 50 and 100 cm depth. The moisture and temperature of the soil were determined at said depth weekly and daily (3 times a day) respectively, during 63 days, time duration of the trial. It was found that the best rooting capacity of those cuttings was obtained when stratified between 20 and 50 cm depth. The oxigen tension at said depth, according to the author, favours the early growth of the buds. Being the huds the main source of auxins and other factors of rooting, they promote the best rizogenesis.